Prevalence and factors associated with non-utilization of healthcare facility for childbirth in rural and urban Nigeria: Analysis of a national population-based survey - Adewuyi, E.; Zhao, Yun; Auta, A.; Lamichhane, R. (2017)
© Author(s) 2017. Aim: The aim of this study was to assess the rural-urban differences in the prevalence and factors associated with non-utilization of healthcare facility for childbirth (home delivery) in Nigeria. Methods: Dataset from the Nigeria demographic and health survey, 2013, disaggregated by rural-urban residence were analyzed with appropriate adjustment for the cluster sampling design of the survey. Factors associated with home delivery were identified using multivariable logistic regression analysis. Results: In rural and urban residence, the prevalence of home delivery were 78.3% and 38.1%, respectively (p < 0.001). The lowest prevalence of home delivery occurred in the South-East region for rural residence (18.6%) and the South-West region for urban residence (17.9%). The North-West region had the highest prevalence of home delivery, 93.6% and 70.5% in rural and urban residence, respectively. Low maternal as well as paternal education, low antenatal attendance, being less wealthy, the practice of Islam, and living in the North-East, North-West and the South-South regions increased the likelihood of home delivery in both rural and urban residences. Whether in rural or urban residence, birth order of one decreased the likelihood of home delivery. In rural residence only, living in the North-Central region increased the chances of home delivery. In urban residence only, maternal age = 36 years decreased the likelihood of home delivery, while 'Traditionalist/other' religion and maternal age < 20 years increased it. Conclusion: The prevalence of home delivery was much higher in rural than urban Nigeria and the associated factors differ to varying degrees in the two residences. Future intervention efforts would need to prioritize findings in this study.